Analysis of gravity-load-designed RC beam-column joints subjected to lateral loads - Lin, Xin (2008)
This study is conducted to model and investigate the behaviour of gravity-load-designed beam-column joints subjected to lateral loads. To achieve different purposes, different models of gravity-load-designed beam-column joints were developed. In finite element analysis, the double panel element was developed and implemented into finite element program, and was corroborated with experiments of typical bond test and beam-column assemblage test. In frame analysis, a model of 12-dof joint element was developed to take into account the softening of the beam-column joint under lateral loads. A model with a combination of spring elements was developed to take into account the fixed-end-rotation at interface between the joint and adjacent members. Analytical results with the two elements were compared with experimental results to show the efficiency and accuracy of newly developed elements. To estimate the shear capacity of beam-column joints, the joint shear strength estimation based on the combination of arch and truss mechanisms was proposed. Finally, the accuracy of the formula was studied through the comparison with the experimental results.